2020
DOI: 10.1080/07391102.2020.1841032
|View full text |Cite
|
Sign up to set email alerts
|

Emerging of composition variations of SARS-CoV-2 spike protein and human ACE2 contribute to the level of infection: in silico approaches

Abstract: SARS-CoV-2 is causative of pandemic COVID-19. There is a sequence similarity between SARS-CoV-2 and SARS-CoV; however, SARS-CoV-2 RBDs (receptor-binding domain) binds 20-fold strongly with human angiotensin-converting enzyme 2 (hACE2) than SARS-CoV. The study aims to investigate protein–protein interactions (PPI) of hACE2 with SARS-CoV-2 RBD between wild and variants to detect the most influential interaction. Variants of hACE2 were retrieved from NCBI and subjected to determine the most pathogenic nsSNPs. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The COVID-19 illness severity has been classified into five zones based on the primary cause (very weak, weak, moderate, strong and very strong). The wild hACE2 receptor and the SARS-CoV-2 spike protein have a tight binding relationship [ 18 ]. A recent study showed that changes in the pH value of 6.5, 7.4, and 8.0 create several conformation states [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 illness severity has been classified into five zones based on the primary cause (very weak, weak, moderate, strong and very strong). The wild hACE2 receptor and the SARS-CoV-2 spike protein have a tight binding relationship [ 18 ]. A recent study showed that changes in the pH value of 6.5, 7.4, and 8.0 create several conformation states [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical Analysis and Cumulative Score Calculation of Pathogenic nsSNPs. In order to predict the high-risk pathogenic nsSNPs of human ACE2, the cumulative score for all software tools (SIFT, PolyPhen2.0, PROVEAN, PANTHER, MUpro, I. Mutant, and ModPred) was calculated by using the Sum function in Excel [21]. Then, we set a restricted cumulative score value; when the result of the seven software tools were combined, the amino acid substitution that was evaluated to be deleterious by at least 6 tools would be identified as ACE2 high-risk pathogenic nsSNPs.…”
Section: Effect On the Stability Of Proteinmentioning
confidence: 99%
“…The SARS-CoV-2 S protein, transmembrane protease serine 2 (TMPRSS2), and human receptor ACE2 are the main determinants of host pathogens affecting infection. The amino acid mutation of S protein, TMPRSS2, and ACE2 binding sites changed the protein affinity, which may affect the structural stability of the complex ( Beacon et al, 2021 ; AlGhamdi et al, 2022 ). Therefore, S glycoprotein and host cell receptor ACE2 are one of the drug targets of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%